2018
DOI: 10.1016/j.molp.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The Flowering Repressor SVP Confers Drought Resistance in Arabidopsis by Regulating Abscisic Acid Catabolism

Abstract: Terrestrial plants must cope with drought stress to survive. Under drought stress, plants accumulate the phytohormone abscisic acid (ABA) by increasing its biosynthesis and decreasing its catabolism. However, the regulatory pathways controlling ABA catabolism in response to drought remain largely unclear. Here, we report that the flowering repressor SHORT VEGETATIVE PHASE (SVP) is induced by drought stress and associates with the promoter regions of the ABA catabolism pathway genes CYP707A1, CYP707A3 and AtBG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 76 publications
3
67
0
1
Order By: Relevance
“…() identified a loss‐of‐function SVP allele conferring rapid flowering for the Yangtze population. This finding also fits the local Yangtze climate because functional SVP contributes to drought resistance (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() identified a loss‐of‐function SVP allele conferring rapid flowering for the Yangtze population. This finding also fits the local Yangtze climate because functional SVP contributes to drought resistance (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the basis of full length amino acid sequence conserved domain and similarity, we subdivided the 171 typical members of the MADS gene family into 5 groups (designated MIKC, Mα, Mβ, Mγ, Mδ), according to the previous classification of MADS proteins from Arabidopsis [9]. Of the 63 inferred physic nut JcMADS proteins, thirty-two were assigned to group MIKC (JcMADS03, 04, 05, 07, 12,16,17,19,20,22,24,25,26,27,28,29,31,32,37,38,42,44,46,47,49,50,52,53,54,55,56,63), thirteen to group Mα (JcMADS01, 06, 08, 11,13,14,33,35,39,43,57,58,59), four to group Mβ (JcMADS09, 48, 51, 60), six to group Mγ (JcMADS10, 15,34,36,41,62) and eight to group Mδ (JcMADS02, 18,21,23,30,40,45,…”
Section: Phylogenetic Relationships Of the Jcmads Proteinsmentioning
confidence: 99%
“…For example, CaMADS-overexpressing Arabidopsis plants show increased resistance of cold and salt stresses [21]. Loss-of-function mutations in SVP result in sensitivity to drought stress, while the SVP-overexpressing plants are more tolerant [22]. In tomato, SlMBP11-RNAi lines are less tolerance to salinity stress, but overexpressing this MADS-box gene confers salt stress tolerance [23].…”
mentioning
confidence: 99%
“…Additionally, the flowering repressor SHORT VEGETATIVE PHASE (SVP) is induced by drought stress and is associated with promoter regions of ABA catabolic pathway genes CYP707A1/3 and AtBG1 . The regulatory pathway involving SVP CYP707A1/3 and AtBG1 plays a critical role in plant drought resistance (Wang, Wang, et al., ). Other researchers have found that overexpression of DWA1 significantly increases cuticular wax deposition in rice, thereby improving the drought resistance of crop varieties (Zhu & Xiong, ).…”
Section: Introductionmentioning
confidence: 99%